Caliban’s Cave: Theatre’s Scandalous Ethics - Liza Kharoubi (Sillages Critiques)
Theatre has often awed philosophers as if it were a dangerous limit to cross: Plato is the perfect example of this dramatic temptation. The reason for this perplexity deserves all possible attention. In this paper, it is contended that Plato’s Complex — the dramatist turned philosopher— unveils a serious ethical issue. Turning the Platonic allegory inside out, I envision Theatre as Caliban’s Cave rather than Prospero’s cell, giving precedence to the slave over the master, to the poetry of shadow over luminescent power. I argue for a philosophy of the Cavern, an attempt to think from the shadows, for which theatre provides a reliable prototype. This theatrical anamorphosis of the myth reveals a political-practical truth rather than a cognitive one. In order to describe this praxis, I invoke the works of some contemporary British and American philosophers who have demonstrated a deep interest in performance matters